From degradation to potential urban regeneration? Residents’ perspectives on a historical neighbourhood in Timişoara, Romania - Camelia Tuţă Adelina; Dragan Alexandru; Creţan Remus (E3S Web of Conferences, 2023)
Recent studies have indicated that residents’ perceptions on urban neighbourhoods are a multidimensional indicator that refers to an individual’s perception of their own position in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns in various social contexts. Our article makes theoretical and empirical contributions to discussions on the perceptions of residents of a historic neighbourhood and how they experience changes in the the context of postsocialist period. Using a questionnaire launched to Timişoara residents (N=480), in the historic district of Fabric, the findings of our study indicate that the degradation of historical buildings, the living space and living conditions are the main causes of dissatisfaction on the part of residents. Although the advantages of the Fabric neighbourhood are its historical heritage and the central location in Timisoara, the state of decay of the historical buildings and the lack of safety are among the major problems of the neighbourhood identified in the narratives of the respondents.